"I'm a stay at home businesswoman": an insight into informal entrepreneurship in Jordan. Issue 1 (30th October 2018) - Mehtap, Salime; Ozmenekse, Leyla; Caputo, Andrea
Abstract : Purpose: Women and disadvantaged minorities within emerging and developing economies often resort to business activity within the informal economy as a way to overcome various barriers and challenges to formal workforce participation. This paper aims to explore the characteristics, motives, barriers and challenges of female engagement in informal business activities in Jordan. Design/methodology/approach: The qualitative analysis used in this paper is based upon empirical findings from semi-structured, in-depth interviews with 14 female informal entrepreneurs in Amman, Jordan. Findings: The study revealed that informal female entrepreneurs tend to be both opportunity- and necessity-driven. Generating profit and contributing to the household income seems to be their main motive. Their businesses were funded either through personal savings or from their social network (e.g. husband, family and friends). Promotion of the business relied mostly on word-of-mouth or social media. High inflation, high competition, time pressures and lack of business skills were cited as the biggest challenges. Besides being content with the status quo, lack of knowledge about the procedures for registering a business and fear of bureaucracy were among the main reasons for not legalizing their activities. Originality/value: There are very few studies that analyse informal micro-entrepreneurship in the Arab world, particularly in the Jordanian context, which is of growing interest due to low number of women in the workforce and the growing number of refugees in the country. This study therefore presents new knowledge around women's informal micro-entrepreneurship in Jordan and provides recommendations for further research and policy-making.